Integration Questions

Question Number 95848 by john santu last updated on 28/May/20

$$\underset{\mathrm{0}} {\overset{\frac{\pi}{\mathrm{2}}} {\int}}\:\frac{\mathrm{dx}}{\sqrt{\mathrm{1}+\mathrm{sin}\:\mathrm{x}}}\:?\: \\$$

Answered by bobhans last updated on 28/May/20

$$\underset{\mathrm{0}} {\overset{\frac{\pi}{\mathrm{2}}} {\int}}\:\frac{\mathrm{dx}}{\sqrt{\left(\mathrm{sin}\:\frac{\mathrm{x}}{\mathrm{2}}+\mathrm{cos}\:\frac{\mathrm{x}}{\mathrm{2}}\right)^{\mathrm{2}} }}\:=\:\underset{\mathrm{0}} {\overset{\frac{\pi}{\mathrm{2}}} {\int}}\:\frac{\mathrm{dx}}{\sqrt{\mathrm{2}}\:\mathrm{cos}\:\left(\frac{\mathrm{x}}{\mathrm{2}}−\frac{\pi}{\mathrm{4}}\right)}\: \\$$$$\mathrm{set}\:\frac{\mathrm{x}}{\mathrm{2}}−\frac{\pi}{\mathrm{4}}\:=\:\mathrm{t}\:\Rightarrow\:\mathrm{dx}\:=\:\mathrm{2}\:\mathrm{dt}\: \\$$$$\underset{−\frac{\pi}{\mathrm{4}}} {\overset{\mathrm{0}} {\int}}\frac{\mathrm{2}\:\mathrm{dt}}{\sqrt{\mathrm{2}\:}\:\mathrm{cos}\:\mathrm{t}}\:=\sqrt{\mathrm{2}}\:\:\left[\mathrm{ln}\:\mid\mathrm{sec}\:\mathrm{t}\:+\:\mathrm{tan}\:\mathrm{t}\:\mid\right]\:_{−\frac{\pi}{\mathrm{4}}} ^{\:\:\mathrm{0}} \\$$$$=\sqrt{\mathrm{2}}\:\:\mathrm{ln}\:\mid\frac{\mathrm{1}+\mathrm{sin}\:\mathrm{t}}{\mathrm{cos}\:\mathrm{t}}\mid\underset{−\frac{\pi}{\mathrm{4}}} {\overset{\mathrm{0}} {\:}}\:=\:\sqrt{\mathrm{2}}\:\left(\mathrm{0}−\mathrm{ln}\left(\sqrt{\mathrm{2}}−\mathrm{1}\right)\right. \\$$$$=\:\sqrt{\mathrm{2}}\:\mathrm{ln}\left(\frac{\mathrm{1}}{\sqrt{\mathrm{2}}−\mathrm{1}}\right)\:=\:\sqrt{\mathrm{2}}\:\mathrm{ln}\:\left(\sqrt{\mathrm{2}}+\mathrm{1}\right)\:\: \\$$

Answered by john santu last updated on 28/May/20

$$\mathrm{let}\:\mathrm{x}\:=\:\frac{\pi}{\mathrm{2}}−\mathrm{t}\:\Rightarrow\begin{cases}{\mathrm{x}=\mathrm{0}\:,\mathrm{t}=\frac{\pi}{\mathrm{2}}}\\{\mathrm{x}=\frac{\pi}{\mathrm{2}},\mathrm{t}=\mathrm{0}}\end{cases} \\$$$$\underset{\frac{\pi}{\mathrm{2}}} {\overset{\mathrm{0}} {\int}}\:\frac{−\mathrm{dt}}{\sqrt{\mathrm{1}+\mathrm{cos}\:\mathrm{t}}}\:=\:\underset{\mathrm{0}} {\overset{\frac{\pi}{\mathrm{2}}} {\int}}\:\frac{\mathrm{dt}}{\sqrt{\mathrm{2cos}\:^{\mathrm{2}} \left(\frac{\mathrm{t}}{\mathrm{2}}\right)}}\: \\$$$$=\:\frac{\mathrm{1}}{\sqrt{\mathrm{2}}}\:\underset{\mathrm{0}} {\overset{\frac{\pi}{\mathrm{2}}} {\int}}\:\mathrm{sec}\:\left(\frac{\mathrm{t}}{\mathrm{2}}\right)\:\mathrm{dt}\:=\:\sqrt{\mathrm{2}}\:\underset{\mathrm{0}} {\overset{\frac{\pi}{\mathrm{2}}} {\int}}\:\mathrm{sec}\:\left(\frac{\mathrm{t}}{\mathrm{2}}\right)\:\mathrm{d}\left(\frac{\mathrm{t}}{\mathrm{2}}\right) \\$$$$=\:\sqrt{\mathrm{2}}\:\mathrm{ln}\:\mid\mathrm{sec}\:\left(\frac{\mathrm{t}}{\mathrm{2}}\right)+\mathrm{tan}\:\left(\frac{\mathrm{t}}{\mathrm{2}}\right)\mid_{\mathrm{0}} ^{\frac{\pi}{\mathrm{2}}} \\$$$$\left.=\sqrt{\mathrm{2}\:\left(\right.}\:\mathrm{ln}\left(\sqrt{\mathrm{2}}\:+\:\mathrm{1}\right)\:−\mathrm{ln}\left(\mathrm{1}\right)\right) \\$$$$=\:\sqrt{\mathrm{2}}\:\mathrm{ln}\:\left(\sqrt{\mathrm{2}}\:+\:\mathrm{1}\:\right)\: \\$$

Answered by 1549442205 last updated on 28/May/20

$$\mathrm{putting}\:\sqrt{\mathrm{1}+\mathrm{sinx}}=\mathrm{t}\Rightarrow\mathrm{t}^{\mathrm{2}} =\mathrm{1}+\mathrm{sinx} \\$$$$\Rightarrow\mathrm{2tdt}=\mathrm{cosxdx}=\sqrt{\mathrm{1}−\left(\mathrm{t}^{\mathrm{2}} −\mathrm{1}\right)^{\mathrm{2}} }\mathrm{dx} \\$$$$=\mathrm{t}\sqrt{\mathrm{2}−\mathrm{t}^{\mathrm{2}} \:\:}\mathrm{dx}.\mathrm{Hence},\mathrm{F}\left(\mathrm{x}\right)=\int\frac{\mathrm{2dt}}{\mathrm{t}\sqrt{\mathrm{2}−\mathrm{t}^{\mathrm{2}} }} \\$$$$\mathrm{putting}\:\sqrt{\mathrm{2}−\mathrm{t}^{\mathrm{2}} }=\mathrm{u}\Rightarrow\frac{−\mathrm{t}}{\sqrt{\mathrm{2}−\mathrm{t}^{\mathrm{2}} }}\mathrm{dt}=\mathrm{du}\Rightarrow−\mathrm{tdt}=\mathrm{udu} \\$$$$\mathrm{F}=\int\frac{−\mathrm{2du}}{\mathrm{2}−\mathrm{u}^{\mathrm{2}} }=\int\frac{\mathrm{2du}}{\mathrm{u}^{\mathrm{2}} −\left(\sqrt{\mathrm{2}}\right)^{\mathrm{2}} }=\frac{\mathrm{1}}{\sqrt{\mathrm{2}}}\mathrm{ln}\mid\frac{\mathrm{u}−\sqrt{\mathrm{2}}}{\mathrm{u}+\sqrt{\mathrm{2}}}\mid \\$$$$\frac{\mathrm{1}}{\sqrt{\mathrm{2}}}\mathrm{ln}\mid\frac{\sqrt{\mathrm{1}−\mathrm{sinx}\:}−\sqrt{\mathrm{2}}}{\sqrt{\mathrm{1}−\mathrm{sin}\:\mathrm{x}}\:+\sqrt{\mathrm{2}}}\mid+\mathrm{C}.\mathrm{Hence}, \\$$$$\mathrm{I}=\mathrm{F}\left(\frac{\pi}{\mathrm{2}}\right)−\mathrm{F}\left(\mathrm{0}\right)=\mathrm{0}−\frac{\mathrm{1}}{\sqrt{\mathrm{2}}}\mathrm{ln}\frac{\sqrt{\mathrm{2}}−\mathrm{1}}{\sqrt{\mathrm{2}}+\mathrm{1}} \\$$$$=−\sqrt{\mathrm{2}}\mathrm{ln}\left(\sqrt{\mathrm{2}}−\mathrm{1}\right)=\sqrt{\mathrm{2}}\mathrm{ln}\left(\sqrt{\mathrm{2}}+\mathrm{1}\right) \\$$

Commented by john santu last updated on 28/May/20

$$\mathrm{oo}\:\mathrm{you}\:\mathrm{change}\:\mathrm{it}\: \\$$

Answered by mathmax by abdo last updated on 28/May/20

$$\mathrm{I}\:=\int_{\mathrm{0}} ^{\frac{\pi}{\mathrm{2}}} \:\frac{\mathrm{dx}}{\sqrt{\mathrm{1}+\mathrm{sinx}}}\:\Rightarrow\mathrm{I}\:=\int_{\mathrm{0}} ^{\frac{\pi}{\mathrm{2}}} \:\frac{\mathrm{dx}}{\sqrt{\mathrm{cos}^{\mathrm{2}} \left(\frac{\mathrm{x}}{\mathrm{2}}\right)+\mathrm{sin}^{\mathrm{2}} \left(\frac{\mathrm{x}}{\mathrm{2}}\right)\:+\mathrm{sin}\left(\frac{\mathrm{x}}{\mathrm{2}}\right)\mathrm{cos}\left(\frac{\mathrm{x}}{\mathrm{2}}\right)}} \\$$$$=\int_{\mathrm{0}} ^{\frac{\pi}{\mathrm{2}}} \:\frac{\mathrm{dx}}{\sqrt{\left(\mathrm{cos}\left(\frac{\mathrm{x}}{\mathrm{2}}\right)+\mathrm{sin}\left(\frac{\mathrm{x}}{\mathrm{2}}\right)\right)^{\mathrm{2}} }}\:=\int_{\mathrm{0}} ^{\frac{\pi}{\mathrm{2}}} \:\frac{\mathrm{dx}}{\mathrm{cos}\left(\frac{\mathrm{x}}{\mathrm{2}}\right)+\mathrm{sin}\left(\frac{\mathrm{x}}{\mathrm{2}}\right)}\:=_{\frac{\mathrm{x}}{\mathrm{2}}=\mathrm{t}} \:\:\int_{\mathrm{0}} ^{\frac{\pi}{\mathrm{4}}} \:\frac{\mathrm{2dt}}{\mathrm{cost}\:+\mathrm{sint}} \\$$$$=_{\mathrm{tan}\left(\frac{\mathrm{t}}{\mathrm{2}}\right)=\mathrm{u}} \:\:\:\:\:\int_{\mathrm{0}} ^{\sqrt{\mathrm{2}}−\mathrm{1}} \:\frac{\mathrm{4du}}{\left(\mathrm{1}+\mathrm{u}^{\mathrm{2}} \right)\left(\frac{\mathrm{1}−\mathrm{u}^{\mathrm{2}} }{\mathrm{1}+\mathrm{u}^{\mathrm{2}} }\:+\frac{\mathrm{2u}}{\mathrm{1}+\mathrm{u}^{\mathrm{2}} }\right)}\:=\mathrm{4}\:\int_{\mathrm{0}} ^{\sqrt{\mathrm{2}}−\mathrm{1}} \:\frac{\mathrm{du}}{\mathrm{1}−\mathrm{u}^{\mathrm{2}} \:+\mathrm{2u}} \\$$$$=−\mathrm{4}\:\int_{\mathrm{0}} ^{\sqrt{\mathrm{2}}−\mathrm{1}} \:\frac{\mathrm{du}}{\mathrm{u}^{\mathrm{2}} −\mathrm{2u}−\mathrm{1}}\:=−\mathrm{4}\:\int_{\mathrm{0}} ^{\sqrt{\mathrm{2}}−\mathrm{1}} \:\frac{\mathrm{du}}{\left(\mathrm{u}−\mathrm{1}\right)^{\mathrm{2}} −\mathrm{2}}\:=−\mathrm{4}\:\int_{\mathrm{0}} ^{\sqrt{\mathrm{2}}−\mathrm{1}} \:\frac{\mathrm{du}}{\left(\mathrm{u}−\mathrm{1}−\sqrt{\mathrm{2}}\right)\left(\mathrm{u}−\mathrm{1}+\sqrt{\mathrm{2}}\right)} \\$$$$=\frac{−\mathrm{4}}{\mathrm{2}\sqrt{\mathrm{2}}}\int_{\mathrm{0}} ^{\sqrt{\mathrm{2}}−\mathrm{1}} \left\{\frac{\mathrm{1}}{\mathrm{u}−\mathrm{1}−\sqrt{\mathrm{2}}}−\frac{\mathrm{1}}{\mathrm{u}−\mathrm{1}+\sqrt{\mathrm{2}}}\right\}\mathrm{du} \\$$$$=−\sqrt{\mathrm{2}}\left[\mathrm{ln}\mid\frac{\mathrm{u}−\mathrm{1}−\sqrt{\mathrm{2}}}{\mathrm{u}−\mathrm{1}+\sqrt{\mathrm{2}}}\mid\right]_{\mathrm{0}} ^{\sqrt{\mathrm{2}}−\mathrm{1}} \:=−\sqrt{\mathrm{2}}\left\{\mathrm{ln}\mid\frac{−\mathrm{2}}{\mathrm{2}\sqrt{\mathrm{2}}−\mathrm{2}}\mid−\mathrm{ln}\mid\frac{\mathrm{1}+\sqrt{\mathrm{2}}}{−\mathrm{1}+\sqrt{\mathrm{2}}}\mid\right\} \\$$$$=−\sqrt{\mathrm{2}}\left\{\mathrm{ln}\mid\frac{\mathrm{1}}{\mathrm{2}−\sqrt{\mathrm{2}}}\mid−\mathrm{ln}\mid\frac{\sqrt{\mathrm{2}}+\mathrm{1}}{\sqrt{\mathrm{2}}−\mathrm{1}}\mid\:=\sqrt{\mathrm{2}}\left\{\mathrm{ln}\left(\mathrm{2}−\sqrt{\mathrm{2}}\right)+\mathrm{ln}\left(\frac{\sqrt{\mathrm{2}}+\mathrm{1}}{\sqrt{\mathrm{2}}−\mathrm{1}}\right)\right\}\right. \\$$